2012
DOI: 10.1002/ejlt.201100296
|View full text |Cite
|
Sign up to set email alerts
|

Virgin rapeseed oils obtained from different rape varieties by cold pressed method – their characteristics, properties, and differences

Abstract: The aim of the present study was to compare different rape varieties. For this purpose oil from six different varieties of rapeseeds was cold pressed under laboratory conditions. In the obtained rapeseed oils the fatty acids composition and minor components, characteristic values (acid value; AV and TOTOX), oxidative stability (DSC test), and volatiles were determined and a sensory evaluation was carried out. The highest oxidative stability was found for oil from sample 5 (IP ¼ 158 min), which also has the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 19 publications
0
18
1
6
Order By: Relevance
“…The pheophytin a content in the oils which were analysed ranged from 1.6 to 10.4 mg/kg in various batches depending on the quality of seeds (Table 3) and it was positively correlated with the impurity content in seeds (r = 0.692). The pheophytin a content determined in the coldpressed oils analysed was higher than the values presented by Tynek et al (2012) (less than 1 mg/kg), but lower than the values reported by Matthäus and Brühl (2003) (20-60 mg/kg). The low content of chlorophyll pigments in cold-pressed oil indicates the full ripeness of processed rapeseeds, in which a reduction in chlorophyll content in the last few days before reaching ripeness may decrease even 100 times (Matthäus, 2012).…”
Section: Physicochemical Properties Of Cold-pressed Oilscontrasting
confidence: 72%
“…The pheophytin a content in the oils which were analysed ranged from 1.6 to 10.4 mg/kg in various batches depending on the quality of seeds (Table 3) and it was positively correlated with the impurity content in seeds (r = 0.692). The pheophytin a content determined in the coldpressed oils analysed was higher than the values presented by Tynek et al (2012) (less than 1 mg/kg), but lower than the values reported by Matthäus and Brühl (2003) (20-60 mg/kg). The low content of chlorophyll pigments in cold-pressed oil indicates the full ripeness of processed rapeseeds, in which a reduction in chlorophyll content in the last few days before reaching ripeness may decrease even 100 times (Matthäus, 2012).…”
Section: Physicochemical Properties Of Cold-pressed Oilscontrasting
confidence: 72%
“…sojowy, słonecznikowy, lniany, ale często niższą niż dziewicza oliwa z oliwek extra virgin [24,27]. Uzyskane wyniki własne były zbliżone do publikowanych w literaturze [6,10,25,26]. Najistotniejszym czynnikiem decydującym o wartości żywieniowej tłuszczów jadalnych jest skład kwasów tłuszczowych.…”
Section: Wyniki I Dyskusjaunclassified
“…Dominującymi kwasami tłuszczowymi w olejach rzepakowych były kwasy: oleinowy (18 : 1), linolowy (18 : 2), -linolenowy (18 : 3), a kwasem charakterystycznym -kwas erukowy (22 : 1). We wszystkich przebadanych olejach udział poszczególnych kwasów tłuszczowych był typowy i charakterystyczny dla oleju rzepakowego niskoerukowego "00", co potwierdza zbieżność z wartościami podanymi w Codex Alimentarius [1] oraz opublikowanymi w literaturze [2,3,4,15,24,25,26]. Wszystkie badane oleje tłoczone na zimno nie zawierały izomerów trans kwasów tłuszczowych w odróżnieniu od oleju rafinowanego, w którym było go 0,8 %.…”
Section: Wyniki I Dyskusjaunclassified
See 2 more Smart Citations